Carmichael Campaign Chorus Book: Community Evangelistic Campaigns - Carmichael, Richard, Rev., 1900-1960; Carmichael, Adele, Rev., 1902-2003 (My University, 1932)
Carmichael, Richard, Rev. and Carmichael, Adele F. "Carmichael Campaign Chorus Book: Community Evangelistic Campaigns," [1932?].
Charmichael, Richard, Rev. and Carmichael, Adele F. "Carmichael Campaign Chorus Book: Community Evangelistic Campaigns," [1932?]. Adele and Richard Carmichael: Series 2, Box 1, Folder 1, ephemera Bethel church years. MS/150/9 Valdosta State University Archives and Special Collections. Bethel Church Assembly of God (Quincy, IL).
Keywords: Bethel Church (Quincy, Ill.); Songbooks; Quincy (Ill.); Clergy; New Age ministers; Pentecostalism; Women evangelists; Evangelistic work; Church musicians